Creation of marginal problems in various knowledge branches as an indicator of growing austerity of lifeworld of personality and society - Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2019)
The creation of a new type of problems (marginal problems) in different branches of scientific knowledge etc., including fundamental scientific problems (S. G. Kara-Murza), difficult problems (A. Asimov), psychological problems (C. G. Jung), complicated problems (M. I. Demchuk, A. T. Yurkevich), existential problems and eternal problems (V. Danchenko), moral problems (H. Lacey, B. G. Yudin), meta-problems of epoch (L. Mlodinov) is considered in the article. The possibilities of interdisciplinary research (synergetics, systemology and science of science) for solving the above mentioned marginal problems are analyzed. The conclusion is substantiated about the presence of strong correlation between the growing actuality of marginal problems and the growing austerity of lifeworld of personality and society.
Keywords: marginal problems; limits and borders of scientific knowledge; society of risk; crisis’s society; horrorology; riskology; risk-management; crisis’s management; sociology of risk; sociology of life; eventology; existential science; «economy of quick responce»; limitology; crisis humanities